Pengaruh Pemberian Kunyit Asam dengan Jus Nanas terhadap Penurunan Nyeri Disminore Primer pada Remaja Putri di TPMB 'M' Belitung Timur - Mawa Datturohma; Fanni Hanifa; Hidayani Hidayani (Pusat riset dan Inovasi Nasional, 2025)
Menstrual pain or dysmenorrhea is a common complaint experienced by adolescent girls throughout the world has shown that the incidence of dysmenorrhea is quite high, namely 43-93% of women experience dysmenorrhea and 5-10% of them experience very severe dysmenorrhea and leave their activities 1-3 days a month, where 8% of them have to leave school or work during menstruation The purpose of this study is to examine the effect of giving turmeric and tamarind with pineapple juice on reducing primary dysmenorrhea pain in TPMB